Regulation of cadherin dimerization by chemical fragments as a trigger to inhibit cell adhesion - Akinobu Senoo (Nature Portfolio, 2021)
Senoo et al. describe a chemical fragment that disrupts dimerization of P-cadherin. In doing so, this fragment inhibits cadherin-mediated cell-adhesion and aggregation.